Measles-Mumps-Rubella vaccine for children with egg allergy: Is admission for inpatient vaccination necessary? - Tan, M S; Teoh, E J; Hor, C P; Yeoh, A A C (Medical journal of Malaysia, 2016)
Children who develop any hypersensitivity reaction to eggs are routinely referred to hospital for Measles-Mumps-Rubella (MMR) vaccination as inpatients to prevent anaphylaxis. We aimed to study the association between hypersensitivity reactions after egg exposure and similar reactions after MMR immunisation; and examine the necessity of hospital admission for vaccination. A prospective observational study was conducted in Paediatric Department in Bukit Mertajam Hospital, Penang, between March and December 2014. Children referred from local polyclinics for inpatient MMR vaccination because of a history of egg allergy were recruited. The children were observed in the ward for post vaccination allergic reactions. Concurrently, a group of children without egg allergy was recruited from those admitted for other illnesses but had recent MMR vaccination at polyclinics. Parents of these children were interviewed and asked if they had observed any reactions post vaccination. In both groups, sociodemographics, medical history and family history of atopy were collected. Eighty-seven subjects were recruited in this study. Fifty-four infants with egg allergy had previous mild allergic reactions after exposure to eggs or egg-related products. They were associated with a family history of egg hypersensitivity, personal history of acute gastroenteritis and upper respiratory tract infections. Two of them developed cutaneous rashes post vaccination during observation, but none developed anaphylactic or anaphylactoid reactions. Two infants among those without egg allergy had post vaccination fever. There was no association between egg allergy and hypersensitivity reactions to MMR vaccine (p=0.632). MMR vaccine can be safely administered to children with mild egg allergy, hence admission for vaccination in the hospital is not warranted. Risk stratification is required to ensure only infants with severe reactions will be admitted for vaccination.